Pure mathematics 1 : Advanced level Mathematicslc/Neill, Hugh - Neill, Hugh.; Quadling, D. A. (england:cambridge,1997, 1997)
Each book covers one syllabus unit (except P2 and P3 which are covered in a combined volume). The syllabus content is arranged in chapters to provide a viable teaching course. Each chapter starts with a list of learning objectives. Mathematical concepts, terminology and notation are explained clearly and carefully. Key results and procedures appear in boxes for easy reference. Stimulating worked examples take a stepby- step approach to problem solving and there are plenty of exercises throughout, as well as revision exercises and practice exam papers.
Introduction; 1. Coordinates, points and lines; 2. Surds and indices; 3. Functions and graphs; 4. Quadratics; 5. Inequalities; Revision exercise 1; 6. Differentiation; 7. Applications of differentiation; 8. Sequences; 9. The binomial theorem; 10. Trigonometry; 11. Combining and inverting functions; 12. Extending differentiation; Revision exercise 2; 13. Vectors; 14. Geometric sequences; 15. Second derivatives; 16. Integration; 17. Volume of revolution; 18. Radians; Revision exercise 3; Practice examinations; Answers; Index
Inclode index
1
Keywords: Mathematics; Mathematics -- Problems, exercises, etc